Analisis Perkembangan Kognitif Terhadap Pola Tingkah Laku Siswa Dalam Kegiatan Pembelajaran Di Sekolah Dasar - Irsan Irsan; Andi Lely Nurmaya. G; Nurdahniar Nurdahniar; Arfandi Arfandi; Fitri Amelia (Jurnal Pendidikan Jompa Indonesia, 2022)
Cognitive development, especially in elementary school age children, is an important thing for a classroom teacher to know and understand. Each child has different cognitive abilities and influences changes in behavior during the learning process. Behavior is essentially a form of students' attitudes in interacting with their learning environment. The purpose of this study was to analyze the cognitive development of students' behavior patterns in learning activities. The method used in this study is a qualitative descriptive approach and using data collection techniques carried out in three ways, namely through document studies, interviews, and observations. The behavior patterns that students show at school during the learning process are, 1) independent behavior, 2) student discipline, 3) curiosity behavior, 4) honest behavior.